Survival nomogram for high-grade bladder cancer patients after surgery based on the SEER database and external validation cohort - Li, Yihe; Chen, Tao; Fu, Bin; Luo, Yixing; Chen, Luyao (Frontiers in Oncology, 2023)
Abstract Background The aim of this study was to develop comprehensive and effective nomogram for predicting overall survival (OS) rates in postoperative patients with high-grade bladder urothelial carcinoma. Methods Patients diagnosed with high-grade urothelial carcinoma of bladder after radical cystectomy (RC) between 2004 and 2015 in the Surveillance, Epidemiology, and End Results (SEER) database were enrolled. We randomly split (7:3) these patients into the primary cohort and internal validation cohort. 218 patients from the First Affiliated Hospital of Nanchang University were collected as the external validation cohort. Univariate and multivariate cox regression analyses were carried out to seek prognostic factors of postoperative patients with high-grade bladder cancer (HGBC). According to these significantly prognostic factors, a simple-to-use nomogram was established for predicting OS. Their performances were evaluated by using the concordance index(C-index), the receiver operating characteristic (ROC) curves, calibration curves and decision curve analysis (DCA). Results The study included 4541 patients. Multivariate Cox regression analysis demonstrated that T stage, positive lymph nodes (PLN), age, chemotherapy, regional lymph nodes examined (RLNE) and tumor size were correlated with OS. The C-index of nomogram in the training cohort, internal and external validation cohort were 0.700, 0.718 and 0.681, respectively. In the training, internal validation and external validation cohorts, the ROC curves showed that the 1-, 3-, and 5-year area under the curve (AUC) were higher than 0.700, indicating that the nomogram had good reliability and accuracy. The results of calibration and DCA showed good concordance and clinical applicability. Conclusions Nomograms were developed for the first time to predict personalized 1-, 3-, and 5-year OS in HGBC patients after RC. The internal and external validation confirmed the excellent discrimination and calibration ability of the nomogram. The nomogram can help clinicians design personalized treatment strategies and assist with clinical decisions.